Formaldehyde assisted reduction achieved p-type orthorhombic tin oxide film prepared by an inexpensive chemical method. (28th November 2017) - Sun, Jian; Chen, Zequn; Nie, Sha; Yu, Zhigen; Yan, Shenghui; Gong, Hao; Tang, Chunhua; Bai, Xue; Xu, Jianmei; Zhao, Ling; Zhou, Wei; Wang, Qing
Abstract: The fabrication of tin oxide thin film of orthorhombic phase has been succeeded under the high pressures from 1.5 GPa to 50 GPa. In this paper, we demonstrate the viability of p-type tin oxide thin film at atmosphere pressure of 0.1 MPa, by a chemical method employing formaldehyde (HCHO) during the annealing process. By using formaldehyde to form formaldehyde-argon mixed reducing ambiance in the chemical sol-gel process, limited oxidation is reached and p-type tin oxide films of orthorhombic phase under ambient pressure are eventually achieved under optimized experimental conditions. Specifically, we have developed a p-type tin oxide thin film with an optimal Hall mobility of 8.6 cm 2 V −1 s −1 . Besides, our results reveal that a Sn rich environment can lead to a higher hole mobility experimentally.